Impacts of revegetation management modes on soil properties and vegetation ecological restoration in degraded sandy grassland in farming-pastoral ecotone - Biao, Fu; Yanbing, Qi; Qingrui, Chang (International Journal of Agricultural and Biological Engineering, 2015)
Focusing on the impact of various vegetation management modes on sandy grassland’s soil property and vegetation ecological restoration of farming-pastoral ecotone, field surveys and lab analysis were conducted to study the correlation between the characteristics of soil properties and vegetation ecological restoration under four different vegetation management modes, i.e., unenclosed natural restoration, enclosed natural restoration, unenclosed artificial restoration and enclosed artificial restoration, which have a restoration history of 15 years in the southern edge of the degraded sandy land area of Mu Us Desert in Leilongwan Town, Hengshan County, Shaanxi Province. After 15 years of vegetation restoration, these four vegetation management modes all proved to be useful for improving the vegetation ecological restoration and the soil quality of the degraded sandy grassland not only by enhancing the aboveground vegetation height, coverage and biomass but also increasing the content of soil clay, organic matter, CEC, total nitrogen, available nutrient while reducing soil bulk density. The vegetation ecological restoration effect and soil quality under enclosed or artificial restoration management are better than those of unenclosed or natural restoration management; and the most satisfactory vegetation ecological restoration effects and soil quality can be achieved under the integration of enclosed and artificial restoration management. Severely degraded sandy grassland, during the vegetation restoration, would form an interactional coordinating relationship with the vegetation and soil properties. Vegetation properties as height, coverage and biomass have significant positive correlations with organic matter, CEC, total nitrogen and available nitrogen, phosphorus, and potassium contained in soil. Only the adoption of the strict enclosure system, implementation of aggressive artificial vegetation restoration measures and the realization of the regurgitation-feeding policy of industry towards husbandry can guarantee the gradual restoration of degraded sandy grassland in farming-pastoral ecotone, so that it can continue to play the role of ecological protective screen. DOI: 10.3965/j.ijabe.20150801.004 Citation: Fu B, Qi Y B, Chang Q R. Impacts of revegetation management modes on soil properties and vegetation ecological restoration in degraded sandy grassland in farming-pastoral ecotone. Int J Agric & Biol Eng, 2015; 8(1): 26－34.